Zmiany ilościowe dna lasu i struktury drzewostanów sosnowych II i III klasy wieku na siedlisku boru świeżego po pożarze pokrywy gleby - Rywka, Piotr (Leśne Prace Badawcze, 2012)
The aim of this study was to determine the effect of fire damage on pine stands by assessing the differences between 24 stands in forest districts of Regional Directorate of Warsaw State Forests. Comparisons were made of the amount of lying dead wood, thickness of forest litter, forest-floor cover by herbaceous plants and shrubs, the density of seedlings, natural seeding regeneration, low and high undergrowth, and the number and condition of stumps in pine stands of 2 nd and 3 rd age classes following 5-6 years after understorey fires. The effect of fire was assessed using a Student’s paired t test to compare mean values before and after fire. Differences in the incidence of traits were tested using an index of non-compliance (AD). In stands of 2nd age class, fire had produced a significant reduction in tree height ( t test, df = 8, t = 2.54, p = 0.0345). In both age classes, there were significant differences between the types of soil surface (burnt, not burnt), but not in humus size, thickness of the upper and lower litter layers, nor in the partially decomposed litter layer. Natural-regeneration density of pine and birch was significantly higher in the burnt than the unburned areas. In stands of 3 rd age class, understorey fires significantly reduced the density of high oak undergrowth.